UPAYA MENINGKATKAN PENDAPATAN DAN STRATEGI BISNIS DI MASA PANDEMI COVID-19 DENGAN MEMANFAATKAN APLIKASI DIGITAL - Mahardhika, Daffa; Putri, Gina Laras; Oktavia, Nova Trisna (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2022)
KuyKuyDrink's business is one of the most in-demand and trending businesses in today's times. Many business actors run this business because the business is in great demand by the public, especially young people. This is evidenced by the increasing number of KuyKuyDrink efforts that stand up from time to time and of course with the characteristic taste of each business. But there are also KuyKuyDrink business actors who have gone out of business or went bankrupt, because the marketing strategy used was not right and the quality of service was less than optimal. The purpose of this study is to find out how the sales method with direct marketing and the use of social media is able to increase the number of sales of KuyKuyDrink drinks. The results of this study show that the increase in sales revenue is not only carried out by direct marketing methods but also social media is one of the media for increasing marketing of this product. With adequate bookkeeping, the owner can make an accurate calculation of the costs incurred so as to reduce the amount of existing costs whose purpose is to obtain the expected profit. Owners are advised to prioritize social media with the aim that the products offered are known to many people, and of course it will also increase income